Assessing Assessment: Toward a Hermeneutic-Phenomenological Perspective - Michael Strawser, PhD (Park University, 2009)
Assessment is generally not a favorite subject for many teachers, and this is likely due to a perceived tension between the goals they wish to accomplish as educators and the methods of assessments prescribed by accrediting agencies. With even President Obama calling for improvements in assessing education, this paper seeks to develop an innovative phenomenological-hermeneutic model of assessment, one that focuses on the first-person interpretation of one's transformative educational experience. After the theoretical framework for developing this model is explained, I present an application of the model through the introduction of "mindful reading assignments."